FAKHR AL-DĪN AL-RĀZĪ ON PLACE. Issue 2 (17th August 2017) - Adamson, Peter
Abstract: The twelfth century philosopher-theologian Fakhr al-Dīn al-Rāzī is well known for his critique of Avicennan metaphysics. In this paper, I examine his critique of Avicenna's physics, and in particular his rejection of the Avicennan and Aristotelian theory of place as the inner boundary of a containing body. Instead, Fakhr al-Dīn defends a definition of place as self-subsisting extension, an idea explicitly rejected by Aristotle and Avicenna after him. Especially in his late work, the Maṭālib, Fakhr al-Dīn explores a number of important philosophical issues with reference to this theory of place, including the principle that two indiscernible things (in this case two overlapping extensions) must be identical and the idea that motion and rest are always relative. Résumé: Le philosophe-théologien du XII e siècle Fakhr al-Dīn al-Rāzī est bien connu pour sa critique de la métaphysique avicennienne. Nous examinons, dans cet article, sa critique de la physique d'Avicenne, et en particulier son rejet de la théorie avicennienne et aristotélicienne du lieu – lieu comme limite interne du corps englobant. Alternativement, Fakhr al-Dīn défend une théorie du lieu comme extension auto-subsistante, doctrine explicitement révoquée par Aristote et Avicenne à sa suite. En particulier dans son œuvre tardive, les Maṭālib, Fakhr al-Dīn explore plusieurs questions philosophiques importantes en rapport avec cette théorie du lieu, dont: le principe voulant que deux choses indiscernables (en l'occurrence deux extensions superposables) soient identiques, et l'idée selon laquelle mouvement et repos sont toujours relatifs.